Experimental study on control performance of tuned liquid column dampers considering different excitation directions. (1st March 2018) - Altunişik, Ahmet Can; Yetişken, Ali; Kahya, Volkan
Highlights: Effectiveness of tuned liquid column dampers (TLCDs) is presented. Evaluation of a structure exposed to ground motions with different directions is performed. TLCDs cause to decrease the resonant frequency and dynamic responses. Damping ratio considerably increases with using TLCD on structures. Abstract: This paper gives experimental tests' results for the control performance of Tuned Liquid Column Dampers (TLCDs) installed on a prototype structure exposed to ground motions with different directions. The prototype structure designed in the laboratory consists of top and bottom plates with four columns. Finite element analyses and ambient vibration tests are first performed to extract the natural frequencies and mode shapes of the structure. Then, the damping ratio of the structure as well as the resonant frequency, head-loss coefficient, damping ratio, and water height-frequency diagram of the designed TLCD are obtained experimentally by the shaking table tests. To investigate the effect of TLCDs on the structural response, the prototype structure-TLCD coupled system is considered later, and its natural frequencies and related mode shapes are obtained numerically. The acceleration and displacement time-histories are obtained by the shaking table tests to evaluate its damping ratio. To consider different excitation directions, the measurements are repeated for the directions between 0° and 90° with 15° increment. It can be concluded from the study that TLCD causes to decrease the resonant frequency of the structure with increasing of the total mass. Damping ratio considerably increases with installing TLCD on the structure. This is more pronounced for the angles of 0°, 15°, 30° and 45°.